2016
DOI: 10.1016/j.solmat.2016.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric function and double absorption onset of monoclinic Cu 2 SnS 3 : Origin of experimental features explained by first-principles calculations

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
50
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 36 publications
13
50
0
Order By: Relevance
“…This is also reflected in the performance of CTS solar cells, since the highest efficiencies are obtained from the monoclinic phase [1], [3]- [5] and consistent band gap values of (0.93 ± 0.02) eV with another optical transition at 1.00 ± 0.03 eV [1]- [5] are reported. The visible second transition is due to the splitting of the valence band and confirms the monoclinic polymorph [13], [14], but does not exclude the simultaneous presence of the cubic polymorph. Another potential problem with CTS is that the net doping is too high for good current extraction [11], [15].…”
Section: Introductionmentioning
confidence: 79%
“…This is also reflected in the performance of CTS solar cells, since the highest efficiencies are obtained from the monoclinic phase [1], [3]- [5] and consistent band gap values of (0.93 ± 0.02) eV with another optical transition at 1.00 ± 0.03 eV [1]- [5] are reported. The visible second transition is due to the splitting of the valence band and confirms the monoclinic polymorph [13], [14], but does not exclude the simultaneous presence of the cubic polymorph. Another potential problem with CTS is that the net doping is too high for good current extraction [11], [15].…”
Section: Introductionmentioning
confidence: 79%
“…All DFTbased calculations were performed with HSE06 and with a cut-off energy of 420 eV. A large k-mesh can be important to describe details in the absorption coefficient [21,22]. However, from test calculations we have found that the effect is not crucial for the considered materials, and we use HSE06 (which avoids incorrect resonance across the underestimated gaps for local potentials [23,24]) and with the same k-mesh as for the calculations of the LDOS.…”
Section: Methodsmentioning
confidence: 99%
“…The main drawback of restricting the applications of Cu-Sn-S compounds in thermoelectrics is their low electrical conductivities (σ) likely due to their wide bandgap (0.93-1.35 eV for Cu 2 SnS 3 , 6,7 1.0~1.80 eV for Cu 3 SnS 4 15-17 and 0.8 eV for Cu 4 Sn 7 S 16 3 ), and inharmonious relation of the Seebeck coefficient (α) and carrier concentration (n H ). Hence it is challenging to significantly improve their TE performance, which is described by the dimensionless figure of merit (ZT), ZT=Tα 2 σ / κ = Tα 2 σ / (κ e +κ L ).…”
Section: Introductionmentioning
confidence: 99%